ANALISIS RASIO KEUANGAN DAN VARIABEL MAKRO TERHADAP RETURN SAHAM (Studi Pada Perusahaan Publik Yang Listing Dalam Indeks Lq 45 Periode 2013-2016) - Muhamad Ramdoni; Rilla Gantino (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2019)
The purpose of this research is to analyze the influence of financial ratio and macro variable to stock return. Total population in this research is 66 companies and obtained 10 companies using purposive sampling method. Technique analysis used is multiple linier regression using panel data. The research shows that return on equity, debt to equity ratio, price earning ratio, and inflation rate simultaneously influence to stock return with value of 6,3 percent. Partially, return on equity has a positive effect to stock return and inflation rate has negative effect to stock return. While the debt to equity ratio and price earning ratio does not affect to stock return.